2019 ACM/IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2019
DOI: 10.1109/esem.2019.8870172
|View full text |Cite
|
Sign up to set email alerts
|

How Different Is It Between Machine-Generated and Developer-Provided Patches? : An Empirical Study on the Correct Patches Generated by Automated Program Repair Techniques

Abstract: Background: Over the years, Automated Program Repair (APR) has attracted much attention from both academia and industry since it can reduce the costs in fixing bugs. However, how to assess the patch correctness remains to be an open challenge. Two widely adopted ways to approach this challenge, including manually checking and validating using automated generated tests, are biased (i.e., suffering from subjectivity and low precision respectively). Aim: To address this concern, we propose to conduct an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Thus, the reputation of a system influences the extent to which humans trust and use that system. Additionally, in the computer science literature, researchers have explored differences in correctness perceptions of machine-generated and human-generated patches [32,33], although this research focused on correctness rather than trust in the system. Trust is inherently different as it refers to the willingness to be vulnerable to the system, rather than the correctness of each patch.…”
Section: Code Reputation and Cognitive Biasesmentioning
confidence: 99%
“…Thus, the reputation of a system influences the extent to which humans trust and use that system. Additionally, in the computer science literature, researchers have explored differences in correctness perceptions of machine-generated and human-generated patches [32,33], although this research focused on correctness rather than trust in the system. Trust is inherently different as it refers to the willingness to be vulnerable to the system, rather than the correctness of each patch.…”
Section: Code Reputation and Cognitive Biasesmentioning
confidence: 99%
“…Le et al [48] assessed the reliability of these two methods and found that a notable part of patches passing the independent test suite are still incorrect while manual validation can suffer from subjectivity. Wang et al [71] further dissected the differences between machinegenerated patches and ground-truth to provide guidance for future manual assessment. Liu et al [21] concluded totally ten common code change patterns from correct patches for further easing this process.…”
Section: Related Workmentioning
confidence: 99%
“…To generate repair patches as simple as possible, has already mentioned in many works [15], [26], [32]. According to a recent study [16] 25.4% (45/177) of the correct patches generated by APR techniques are syntactically different from developer provided ones. Other approaches also exists, which generate patches by learning human-written program codes [33], [34].…”
Section: Related Workmentioning
confidence: 99%